1998
DOI: 10.1128/aem.64.7.2409-2417.1998
|View full text |Cite
|
Sign up to set email alerts
|

Role of Organic Acids in the Manganese-Independent Biobleaching System of Bjerkandera sp. Strain BOS55

Abstract: Bjerkandera sp. strain BOS55 is a white rot fungus that can bleach EDTA-extracted eucalyptus oxygen-delignified kraft pulp (OKP) without any requirement for manganese. Under manganese-free conditions, additions of simple physiological organic acids (e.g., glycolate, glyoxylate, oxalate, and others) at 1 to 5 mM stimulated brightness gains and pulp delignification two- to threefold compared to results for control cultures not receiving acids. The role of the organic acids in improving the manganese-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…For the in vivo decolorization, 5 ml of the synthetic textile effluent (pH 8Á1) was added to the Erlenmeyer flasks containing the microorganism cultivated in synthetic medium, and the medium decolorization was assessed after 24 h. For the in vitro decolorization, the content of the Erlenmeyer flasks was filtered to obtain free cell extracts. The presence of H 2 O 2 in the enzymatic extract was determined using horseradish peroxidase (Moreira et al 1998). Then, 5 ml of the synthetic textile effluent was added to the extracts, and the decolorization was verified during several time intervals, up to 24 h. The colour reduction was determined spectrophotometrically at 625 nm.…”
Section: Dye Decolorization In Liquid Mediummentioning
confidence: 99%
“…For the in vivo decolorization, 5 ml of the synthetic textile effluent (pH 8Á1) was added to the Erlenmeyer flasks containing the microorganism cultivated in synthetic medium, and the medium decolorization was assessed after 24 h. For the in vitro decolorization, the content of the Erlenmeyer flasks was filtered to obtain free cell extracts. The presence of H 2 O 2 in the enzymatic extract was determined using horseradish peroxidase (Moreira et al 1998). Then, 5 ml of the synthetic textile effluent was added to the extracts, and the decolorization was verified during several time intervals, up to 24 h. The colour reduction was determined spectrophotometrically at 625 nm.…”
Section: Dye Decolorization In Liquid Mediummentioning
confidence: 99%
“…These results suggest that LiP, but not MnP, is involved in the brightening of E-OKP by whiterot fungi under Mn(II)-less culture conditions. Moreira et al, reported that an increase in the physiological concentration of VA and oxalate as well as an enhancement of MnP and LiP production were observed, and that these factors contributed to greatly improved production of superoxide anion radicals, which may have accounted for the more extensive biobleaching observed [11]. However, since Mn(II) is essential for the production of superoxide anion radicals under the MnP reaction system [12,13], it is questionable whether superoxide anion radicals were produced under Mn(II)-free culture conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that LiP plays an important role in the brightening of manganese-less E-OKP by both P. sordida YK-624 and P. chrysosporium under Mn(II)-free culture conditions. Moreira et al, reported that the addition of simple physiological organic acids results in two-to three-fold gains in brightness compared with control cultures without organic acids, and that the stimulation is attributed to enhanced production of MnP and LiP ( [11]). Therefore, the effect of malonate and glyoxylate addition on the brightening of E-OKP by P. sordida YK-624 was examined ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxalate appears to have versatile roles in fungi. It has been proposed to have an important connection with manganese peroxidase (MnP) and manganese in the oxidation of aromatics (Lequart et al ., 1998; Moreira et al ., 1998; Shimada et al ., 1994). Oxalate can also function in lignin peroxidase (LiP) systems (Popp et al ., 1990).…”
Section: Biochemical Molecular and Genomic Studies On H Annosum–conmentioning
confidence: 99%